C++ FAQs : Frequently asked questions - Cline, Marshall P.; Lomow, Greg
A reference source containing answers to common C++ programming problems. Inspired by the success of FAQ, originally available on the Internet, the format of this book is designed to make information accessible. It includes four to five times the material of the electronic FAQ.